Wound Healing Properties of Selected Plants Used in Ethnoveterinary Medicine - Marume, Amos; Matope, Gift; Katsande, Simbarashe; Khoza, Star; Mutingwende, Isaac; Mduluza, Takafira; Munodawafa-Taderera, Tafadzwa; Ndhlala, Ashwell R. (Frontiers in Pharmacology, 2017)
Plants have arrays of phytoconstituents that have wide ranging biological effects like antioxidant, anti-inflammatory and antimicrobial properties key in wound management. In vivo wound healing properties of ointments made of crude methanolic extracts (10% extract w/w in white soft paraffin) of three plant species, Cissus quadrangularis L. (whole aerial plant parts), Adenium multiflorum Klotzsch (whole aerial plant parts) and Erythrina abyssinica Lam. Ex DC. (leaves and bark) used in ethnoveterinary medicine were evaluated on BALB/c female mice based on wound area changes, regular observations, healing skin’s percentage crude protein content and histological examinations. White soft paraffin and 3% oxytetracycline ointment were used as negative and positive controls respectively. Wound area changes over a 15 day period for mice treated with C. quadrangularis and A. multiflorum extract ointments were comparable to those of the positive control (oxytetracycline ointment). Wounds managed with the same extract ointments exhibited high crude protein contents, similar to what was observed on animals treated with the positive control. Histological evaluations revealed that C. quadrangularis had superior wound healing properties with the wound area completely returning to normal skin structure by day 15 of the experiment. E. abyssinica leaf and bark extract ointments exhibited lower wound healing properties though the leaf extract exhibited some modest healing properties.